Molecular Characterization and Phylogenetic Analysis of the 2019 Dengue Outbreak in Wenzhou, China - Han, Axiang; Sun, Baochang; Sun, Zhewei; Xu, Xuelian; Yang, Qiongying; Xie, Danli; Guan, Wanchun; Lou, Yongliang (Frontiers in Cellular and Infection Microbiology, 2022)
In 2019, a dengue outbreak occurred with 290 confirmed cases in Wenzhou, a coastal city in southeast China. To identify the origin of the dengue virus (DENV) from this outbreak, viral RNA was extracted from four serum samples and sequenced for whole genome analysis. Then, phylogenetic analysis, gene mutation, secondary structure prediction, selection pressure analysis, and recombination analysis were performed. DENV strains Cam-03 and Cam-11 were isolated from patients traveling from Cambodia, while ZJWZ-18 and ZJWZ-62 strains were isolated from local patients without a record of traveling abroad. The whole genome sequence of all four strains was 10,735 nucleotides long. Phylogenetic tree analysis showed that the four strains belonged to genotype 1 of DENV-1, but the local Wenzhou strains and imported strains clustered in different branches. ZJWZ-18 and ZJWZ-62 were closely related to strain MF033254-Singapore-2016, and Cam-03 and Cam-11 were closely related to strain AB608788-China : Taiwan-1994. A comparison of the coding regions between the local strains and the DENV-1 standard strain (EU848545-Hawaii-1944) showed 82 amino acid mutations between the two strains. A total of 55 amino acid mutations were found between the coding regions of the local and imported strains. The overall secondary structure of the 3′ UTR of the local strains had changed: apparent changes in the head and tail position were observed when compared to DENV-1 standard strain. Furthermore, selection pressure analysis and recombination detection using the 4 isolates and 41 reference strains showed two credible positive selection sites and eight credible recombination events, which warrant further studies. This study may enhance the understanding of viral replication, infection, evolution, virulence, and pathogenicity of DENV.